EVALUASI PENGGUNAAN SISTEM E-PUSKESMAS - Rini Jusy Fitriana; Galih Persadha; Nur Hanida; Deyana Amalia (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
The rapid development of information technology is marked by the use of computers as a means of supporting human activities. The implementation of the E-Puskesmas application, web-based and mobile, helps in health center services and management according to the standards of the Ministry of Health. The PIECES framework has six categories, helping in solving system problems with effectiveness. The results of the study showed a high level of user satisfaction of the E-Puskesmas system, with an average value of the variables Performance, Information, Economy, and Service above 80%. Although there are several obstacles such as natural networks and systems, the Implementation of E-Puskesmas with the PIECES approach in Puskesmas has been running well, improving the quality of service and user satisfaction